Autonomy new catchword in education system - Abd Razak, Dzulkifli (2007)
IT is very refreshing to see that the word "autonomy" has crept back into the academic world. With cluster schools becoming a reality, education history is being created, with autonomy the mainstay for the successful implementation of the concept. Some are even surprised at the degree of autonomy allowed, saying this has never happened before in the education system. For too long "autonomy" has been regarded as a taboo or dirty word when it comes to education. Now, all of a sudden, a school can actually hire a badminton coach if it wants to churn out badminton champions, have its own special training programmes or seek collaboration with major IT companies to enhance the school's computer facilities to keep up with new advances (NST, March 24).